Manifestasi Penyakit Kulit pada Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Dr. Pirngadi Medan - Dione Larissa Simanjuntak; Kristo Nababan; Joseph Sibarani (Nommensen Journal of Medicine, 2021)
Background: Diabetes mellitus (DM) is a metabolic group with characteristic hyperglycemia that occurs due toabnormal insulin secretion, insulin action, or both. DM is often called the silent killer because the patients knowthey has DM only after the patient experiencing complications and manifestations. It is estimated that 30-70% of DM patients experience skin manifestations during the disease process. The relationship between the appearance of skin manifestations with diabetes mellitus is not yet known, but it is suspected due to chronic hyperglycemia and abnormalities of the immune system.Objective: To determine skin diseases in patients with type 2 diabetes at General Hospital Dr. Pirngadi Medan.Methods: This research was a descriptive study with a cross-sectional study design conducted at Dr. GeneralHospital Pirngadi Medan. Data collection was carried out through 29 medical records of patients with diabetesmellitus from January 2018 to December 2018. Samples were selected by total sampling.Results: From 29 samples studied, there were six types of skin manifestations. The most common skinmanifestations are Diabetic Ulcer (62.07%), followed by Steven Johnson Syndrome and diabetic gangrene, which both are equally 13.80%. The other skin manifestations are herpes zoster, gluteal abscess, and bullous pemphigoid (3.44%).Conclusion: The most common manifestation of the skin in patients with type 2 DM is Diabetic Ulcer.